Reviving and Refining Psychodynamic Interpretation of the Wechsler Intelligence Tests: The Verbal Comprehension Subtests. Issue 3 (4th May 2017) - Bram, Anthony D.
ABSTRACT: The Wechsler intelligence tests (currently Wechsler, 2008, 2014) have traditionally been part of the multimethod test battery favored by psychodynamically oriented assessors. In this tradition, assessors have used Wechsler data to make inferences about personality that transcend cognition. Recent trends in clinical psychology, however, have deemphasized this psychodynamic way of working. In this article, I make a conceptual and clinical case for reviving and refining a psychodynamic approach to inference making about personality using the Wechsler Verbal Comprehension subtests. Specifically, I (a) describe the psychological and environmental conditions sampled by the Wechsler tests, (b) discuss the Wechsler tests conceptually in terms of assessing vulnerability to breakdowns in adaptive defensive functioning, (c) review a general framework for inference making, and (d) offer considerations for and illustrate pragmatic application of the Verbal Comprehension subtests data to make inferences that help answer referral questions and have important treatment implications.